DIGITAL LEARNING IN HIGHER EDUCATION: THE NEW PARADOX OF COLLECTIVISM AND ISOLATION AMONG STUDENTS - Bharaty, Dr. Samaresh; Das, Sarthik (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The prevalence of digital learning in higher education presents a dichotomy between collectivism and isolation among students. On the one hand, digital platforms provide unprecedented opportunities for collaborative and shared learning experiences, thereby fostering a sense of collegiality. On the other hand, these technologies can lead students to experience a sense of isolation and disconnection during their educational journey in virtual environments. This paper explores the paradox of how digital learning reshapes social interactions, influences student engagement, and thereby affects students' overall educational experience.